2017
DOI: 10.1097/jsa.0000000000000134
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Bone Marrow Stimulation Techniques

Abstract: Marrow stimulation techniques, including microfracture, are among the most commonly performed cartilage restoration procedures for symptomatic chondral defects of the knee. For the vast majority of patients, marrow stimulation results in reduced pain and improved function, providing overall satisfactory outcomes. In some cases, however, marrow stimulation fails, resulting in symptom recurrence and often, the need for repeat surgery. This review will describe the indications and outcomes of microfracture as a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…Focal cartilage defects of the knee are commonly treated with marrow stimulation techniques, which have been shown to have inferior long-term clinical outcomes due in large part to the predominantly fibrocartilage repair tissue generated. [5][6][7] Fibrocartilage has poor compressive stiffness under load, inferior resilience and inferior wear characteristics than hyaline cartilage. 8 Recently, bone marrow aspirate concentrate (BMAC) has been investigated as both a primary therapeutic as well as an augmentation to existing cartilage restoration procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Focal cartilage defects of the knee are commonly treated with marrow stimulation techniques, which have been shown to have inferior long-term clinical outcomes due in large part to the predominantly fibrocartilage repair tissue generated. [5][6][7] Fibrocartilage has poor compressive stiffness under load, inferior resilience and inferior wear characteristics than hyaline cartilage. 8 Recently, bone marrow aspirate concentrate (BMAC) has been investigated as both a primary therapeutic as well as an augmentation to existing cartilage restoration procedures.…”
Section: Introductionmentioning
confidence: 99%
“…13,24 Recent reviews have raised concerns about the long-term durability of microfracture in other joints, and it is important to characterize these outcomes for the glenohumeral joint. 7,[13][14][15] Long-term outcomes after microfracture of the glenohumeral joint are unclear. The purpose of this study is to provide updated long-term clinical follow-up on a previously reported cohort of patients who underwent microfracture for symptomatic articular cartilage defects of the glenohumeral joint.…”
mentioning
confidence: 99%
“…Focal chondral defects (FCDs) of the knee joint are common, occurring in over 60% of patients undergoing knee arthroscopic surgery. 1,7,9,13,18,26 FCDs have limited regenerative potential in response to injuries, as articular cartilage is relatively avascular and aneural. 12,13,26 Untreated FCDs within the knee joint can result in mechanical symptoms that impair function or cause pain and effusion, especially when located on weightbearing surfaces of the medial or lateral compartments.…”
mentioning
confidence: 99%
“…1,7,9,13,18,26 FCDs have limited regenerative potential in response to injuries, as articular cartilage is relatively avascular and aneural. 12,13,26 Untreated FCDs within the knee joint can result in mechanical symptoms that impair function or cause pain and effusion, especially when located on weightbearing surfaces of the medial or lateral compartments. 13 In contrast, osteoarthritis (OA) of the knee joint is characterized by progressive loss of articular cartilage, osteophytes, subchondral cysts, joint space narrowing, and intermittent inflammation of the joint tissues.…”
mentioning
confidence: 99%